2011
DOI: 10.2165/11593140-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Respiratory Syncytial Virus

Abstract: Respiratory syncytial virus (RSV) is a highly contagious virus, and is the major cause of lower respiratory tract infections in infants and toddlers worldwide.RSV infection poses serious health risks to young children during the first 2 years of life. Several infant populations have been classified as high risk, and additional risk factors are known to increase the likelihood of severe RSV infection. Treatment for active RSV infection is limited to the symptoms of infection rather than the underlying cause; th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 73 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…Six articles provided detailed information on specific symptoms, impacts, and experiences associated with RSV in adult patients [ 3 , 14 18 ]. Desktop research identified nine additional articles or websites [ 2 , 5 , 6 , 19 24 ]. Table 1 details all signs, symptoms, and impacts of RSV infection identified in the literature, including impact on daily activities and emotions contained in the Flu-iiQ.…”
Section: Resultsmentioning
confidence: 99%
“…Six articles provided detailed information on specific symptoms, impacts, and experiences associated with RSV in adult patients [ 3 , 14 18 ]. Desktop research identified nine additional articles or websites [ 2 , 5 , 6 , 19 24 ]. Table 1 details all signs, symptoms, and impacts of RSV infection identified in the literature, including impact on daily activities and emotions contained in the Flu-iiQ.…”
Section: Resultsmentioning
confidence: 99%
“…Treatment with JNJ-8678 administered for 7 days was well tolerated and, importantly, there were no new safety signals in this pediatric population compared with previous studies in healthy adults. Reported AEs were symptoms not uncommon in infants and typical of those which present during RSV infection [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a severe viral infection, diarrhea could be caused by a direct enterocyte virus infection (such as RSV) [ 13 ] and/or sepsis-associated factors (cytokinemia, endotoxemia, and gut dysbiosis), as demonstrated in severe dengue infection [ 14 , 15 ]. As such, hypercytokinemia in sepsis induces the breakdown of intestinal tight junctions (TJs), allowing the translocation of PAMPs from the gut into blood circulation (gut translocation) [ 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%